Spiritual Consumption Culture in the Digital Age: Islamic Influencers and New Ethics of Piety among Students at Diponegoro University - Wibowo, Arif (Jurnal Keislaman, 2026)
This study examines the dynamics of culture spiritual consumption among students at Diponegoro University (Undip) in the digital age, particularly through their interactions with Islamic influencers on social media. Using a qualitative approach, ethnographic observation, and in-depth interviews with 50 students, this study found that the consumption of digital religious content is not only an informative activity but also a practice of identity formation, online community building, and the performance of piety. The platforms most frequently used by students are YouTube, with 19 users or 38%, Instagram with 15 users or 30%, TikTok with 11 users or 22%, X with 3 users or 6%, and Facebook with 2 users or 4%. From this data, we can conclude that the digital platforms most frequently used by students to view religious content are YouTube, followed by Instagram, TikTok, X, and finally Facebook. Among these digital platforms, the themes they view and delve into are: ethics/Akhlak (hablu min Allah, hablu min An naas) with 23 people or 46%, Prophetic Biography (Sirah Nabawiyah) by 10 people or 20%, Fiqh by 9 people or 18%, Motivation by 5 people or 10%, and Quran and Hadith by 3 people or 6%. The spiritual influencers that Undip students refer to for deepening their Islamic spirituality are: Ustadz Hanan Attaki (UHA) with 16 people or 32%, Ustadz Adi Hidahat (UAH) and Habib Ja’far al Hadar, both with 12 people or 24% each, Ustadz Abdul Somad (UAS) with 7 people or 14%, and Ustadz Felix Siauw with 3 people or 6%. Islamic influencers act as new authority figures presenting piety in a personal and visual style. Students construct digital religious ethics through new contextual codes of conduct and demonstrate critical attitudes toward the commodification of da'wah. These findings indicate a transformation of the meaning of piety into a social practice integrated with technology and popular culture. These findings contribute to the study of digital Islam and religious ethics among young people in Indonesia.